New insights into hydrothermal vent processes in the unique shallow-submarine arc-volcano, Kolumbo (Santorini), Greece - Kilias, Stephanos P.; Nomikou, Paraskevi; Papanikolaou, Dimitrios; Polymenakou, Paraskevi N.; Athanasios Godelitsas; Argyraki, Ariadne; Carey, Steven; Gamaletsos, Platon; Theo J. Mertzimekis; Stathopoulou, Eleni; Goettlicher, Joerg; Steininger, Ralph; et al. (Sci. Rep., 2013)
We report on integrated geomorphological, mineralogical, geochemical and biological investigations of the hydrothermal vent field located on the floor of the density-stratified acidic (pH   5) crater of the Kolumbo shallow-submarine arc-volcano, near Santorini. Kolumbo features rare geodynamic setting at convergent boundaries, where arc-volcanism and seafloor hydrothermal activity are occurring in thinned continental crust. Special focus is given to unique enrichments of polymetallic spires in Sb and Tl (±Hg, As, Au, Ag, Zn) indicating a new hybrid seafloor analogue of epithermal-to-volcanic-hosted-massive-sulphide deposits. Iron microbial-mat analyses reveal dominating ferrihydrite-type phases, and high-proportion of microbial sequences akin to "Nitrosopumilus maritimus", a mesophilic Thaumarchaeota strain capable of chemoautotrophic growth on hydrothermal ammonia and CO2. Our findings highlight that acidic shallow-submarine hydrothermal vents nourish marine ecosystems in which nitrifying Archaea are important and suggest ferrihydrite-type Fe3+-(hydrated)-oxyhydroxides in associated low-temperature iron mats are formed by anaerobic Fe2+-oxidation, dependent on microbially produced nitrate.